Integrated Resistivity and Ground Penetrating Radar Observations of Underground Seepage of Hot Water at Blawan-Ijen Geothermal Field - Sukir Maryanto; Ika Karlina Laila Nur Suciningtyas; Cinantya Nirmala Dewi; Arief Rachmansyah (International Journal of Geophysics)
Geothermal resource investigation was accomplished for Blawan-Ijen geothermal system. Blawan geothermal field which located in the northern part of Ijen caldera presents hydrothermal activity related with Pedati fault and local graben. There were about 21 hot springs manifestations in Blawan-Ijen area with calculated temperature about 50°C. We have performed several geophysical studies of underground seepage of hot water characterization. The geoelectric resistivity and GPR methods are used in this research because both of them are very sensitive to detect the presence of hot water. These preliminary studies have established reliable methods for hydrothermal survey that can accurately investigate the underground seepage of hot water with shallow depth resolution. We have successfully identified that the underground seepage of hot water in Blawan geothermal field is following the fault direction and river flow which is evidenced by some hot spring along the Banyu Pahit river with resistivity value less than 40 Ωm and medium conductivity.